Role of B7 family members in glioma: Promising new targets for tumor immunotherapy - Wang, Yan; Li, Mengxi; Wang, Gang; Wu, Hui (Frontiers in Oncology, 2023)
Glioma, is a representative type of intracranial tumor among adults, usually has a weak prognosis and limited treatment options. Traditional therapies, including surgery, chemotherapy, and radiotherapy, have had little impact on patient survival time. Immunotherapies designed to target the programmed cell death protein 1 (PD-1)/programmed death ligand 1 (PD-L1) signaling pathway have successfully treated various human cancers, informing the development of similar therapies for glioma. However, anti-PD-L1 response rates remain limited in glioma patients. Thus, exploring novel checkpoints targeting additional immunomodulatory pathways for activating durable antitumor immune responses and improving glioma outcomes is needed. Researchers have identified other B7 family checkpoint molecules, including PD-L2, B7-H2, B7-H3, B7-H4, and B7-H6. The current review article evaluates the expression of all 10 reported members of the B7 family in human glioma using The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) data, as well as summarizes studies evaluating the clinical meanings and functions of B7 family molecules in gliomas. B7 family checkpoints may contribute to different immunotherapeutic management options for glioma patients.